Re-evaluation of Padre Secchi’s visual method for modern oceanography - Hänninen, Jari; Sahlstén, Johannes (Frontiers in Marine Science, 2024)
Secchi-disk is an instrument that enables investigating water transparency, being reflective of sunlight to be used to measure the depth of light penetration in the water column. In biological marine research, the device is used to determine the intensity of primary production of planktonic algae. In the present study, we re-evaluated the practicality of Secchi’s method, developed some 160 years ago, for modern oceanography by using the same locations, methods, objectives, and comparable Secchi disk that were used in his survey in 1865. We show that the Secchi-disk is still a valid scientific method in environmental marine research and therefore defends its place reliably among modern electronical research infrastructure. Observer’s subjectivity didn’t have a significant effect on measuring but environmental conditions can influence ZSD determination in general. It is therefore justified to follow, for example, the general recommendations for the use of the Secchi net issued by HELCOM. Our results also revealed that ZSD was located about twofold deeper in 1865 than presently which cannot be explained only by annual variation. We show that green(ish) sea areas have today extended to larger sea areas than they were 160 years ago, due to an increase in the turbidity of the water resulting from, e.g., general eutrophication.